Comparative Proteomics of Leaves from Phytase-Transgenic Maize and Its Non-transgenic Isogenic Variety - Tan, Yanhua; Yi, Xiaoping; Wang, Limin; Peng, Cunzhi; Sun, Yong; Wang, Dan; Zhang, Jiaming; Guo, Anping; Wang, Xuchu (Frontiers in Plant Science, 2016)
To investigate unintended effects in genetically modified crops (GMCs), a comparative proteomics analysis between the leaves of the phytase-transgenic maize and those of non-transgenic plants was performed by using two-dimensional gel electrophoresis and mass spectrometry. A total of 57 differentially expressed protein spots (DEPs) were successfully identified, which represented 44 unique proteins. Functional classification of the identified unique proteins showed that these proteins were predominantly involved in carbohydrate transport and metabolism, followed by post-translational modification. KEGG pathway analysis revealed that most of the DEPs participated in carbon fixation in photosynthesis. Comparison of the changes in the protein and gene transcript levels of the identified unique proteins showed that most proteins had a similar pattern of changes between proteins and transcripts. Our results suggested that although some significant differences were observed, the proteomic patterns were not substantially altered between the leaves of phytase-transgenic maize and its non-transgenic isogenic type. Moreover, none of the DEPs was identified as a new toxic protein or an allergenic protein. The differences of proteome between the two kinds of maize leaves might be attributed to both genetic modification and hybrid influence.